2015
DOI: 10.5551/jat.26690
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Arterial Stiffness and Gender-specific Differences in the Relationships with Classical Cardiovascular Risk Factors

Abstract: Aim:To investigate the relationships between arterial stiffness and classic cardiovascular risk factors with respect to gender differences in addition to the prevalence of high arterial stiffness in Chongqing, China based on an examination of 18,336 subjects. Methods: The cardio-ankle vascular index was used as a marker of arterial stiffness. The relationships between arterial stiffness and body mass index (BMI) as well as metabolic syndrome (MetS) were estimated using logistic regression models. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
6
9
1
1
Order By: Relevance
“…Os dois estudos mais bem delineados sobre esse desfecho, ambos conduzidos com pacientes chineses, apontam prevalências de 12,7% e 22,3% para homens e de 9,9% e 26,4% para mulheres 49,50 . Ainda que se note uma alta variabilidade entre esses dois estudos, ambos apresentam valores de prevalência menores do que os obtidos para Vitória (57,9%).…”
Section: Discussionunclassified
“…Os dois estudos mais bem delineados sobre esse desfecho, ambos conduzidos com pacientes chineses, apontam prevalências de 12,7% e 22,3% para homens e de 9,9% e 26,4% para mulheres 49,50 . Ainda que se note uma alta variabilidade entre esses dois estudos, ambos apresentam valores de prevalência menores do que os obtidos para Vitória (57,9%).…”
Section: Discussionunclassified
“…The cardio‐ankle vascular index (CAVI) was used as a marker of arterial stiffness (Wen et al . ). Interestingly, they also point at significant gender differences in the prevalence of high artery stiffness by showing that for all age brackets, the effect of age was stronger in men, confirming earlier reports in a Japanese population (Hirasada et al .…”
Section: Arterial Stiffness: Mechanisms Risk Factors and Clinical Asmentioning
confidence: 97%
“…The study of Wen also revealed that having elevated systolic blood pressure was associated with a higher prevalence of stiffness in women than in men (Wen et al . ). With prevalence being higher in the overall elderly group (39.17%) compared to middle‐aged (6.81%) and young subjects (0.99%) (Wen et al .…”
Section: Arterial Stiffness: Mechanisms Risk Factors and Clinical Asmentioning
confidence: 97%
See 2 more Smart Citations